2004
DOI: 10.1097/01.coc.0000071467.96942.2f
|View full text |Cite
|
Sign up to set email alerts
|

Adriamycin and Cis-Platinum as First-Line Treatment in Unresectable Locally Advanced or Metastatic Adult Soft-Tissue Sarcomas

Abstract: Standard chemotherapy in advanced adult soft-tissue sarcomas (STS) has not yet been established. We evaluated the efficacy and toxicity of the combination of adriamycin (ADR) and cis-platinum (CDDP) as first-line treatment in nonoperable locally advanced or metastatic adult STS. Thirty patients were treated with CDDP 100 mg/m2 on day 1 and ADR 75 mg/m2 equally divided on days 1 to 3, every 3 weeks for 6 cycles. Patients were evaluated for response, toxicity, and survival, while resectability of residual diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…Besides, targeting the HR and non-homologous end-joining (NHEJ) mechanism of cancer cell might further enhance such therapeutic sensitivity of the cancer cells with high levels of CNVs (Gregg et al, 1993;Zhang et al, 2014). However, previous clinical trials of PARPi and DNA-damaging agents mostly failed to confirm such vulnerability in unselected sarcoma population (Kalofonos et al, 2004;Choy et al, 2014). Interestingly, our study demonstrated that genomic instability and BRCAness phenotype could vary tremendously, both inter-and intrain STS subtypes, which were correlative with tumoral MCM4 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, targeting the HR and non-homologous end-joining (NHEJ) mechanism of cancer cell might further enhance such therapeutic sensitivity of the cancer cells with high levels of CNVs (Gregg et al, 1993;Zhang et al, 2014). However, previous clinical trials of PARPi and DNA-damaging agents mostly failed to confirm such vulnerability in unselected sarcoma population (Kalofonos et al, 2004;Choy et al, 2014). Interestingly, our study demonstrated that genomic instability and BRCAness phenotype could vary tremendously, both inter-and intrain STS subtypes, which were correlative with tumoral MCM4 expression.…”
Section: Discussionmentioning
confidence: 99%
“…G and A were used in combination in a phase I/II trial on transitional cell carcinomas of the urothelial tract that demonstrated a good toxicity profile and promising activity. A and P have been combined in the treatment of endometrial carcinoma and sarcoma [4,5]. A phase II study of the same combination in 18 patients with renal cell carcinoma reported two complete responses (CRs) and five PRs with no grade 4 toxicities [2].…”
Section: Introductionmentioning
confidence: 99%
“…4 A variety of combination regimens has been studied in phase II and III trials and most of them have included adriamycin. [5][6][7][8] Most of these studies have suggested that combination chemotherapy may result in higher response rates than single-agent doxorubicin. Epirubicin, which is an analogue of doxorubicin with less cardiotoxicity but equal efficacy, 9 has been used as single agent and in combination regimens for the treatment of STS.…”
Section: Introductionmentioning
confidence: 99%